Application of non-specific esterase enzyme microassays to detect potential insecticide resistance of Aedes aegypti adults in Yogyakarta, Indonesia - Sugeng Juwono Mardihusodo, Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
By bioassay Aedes aegypti larvae collected from Yogyakarta were found to be susceptible to temephos and malathion and by using microplate enzymatic assay Ae. aegypti larvae collected from the same sites were potentially resistant to the organophosphate insecticides due to elevated esterase activity in hydrolyzing a-naphthyl acetate substrate used in the enzymatic reaction from the same sites might be potentially resistant to OP insecticides due to the same mechanism. The homogenates of the mosquito adult stages from the fields were microassayed using a-naphthyl acetate substrate compared to that colonized in the laboratory. From a series of studies the results were concluded that Ae. aegypti adults in Yogyakarta were susceptible and potentially resistant to insecticides due to elevated a-naphthyl acetate esterase activity.Key words: Aedes aegypti - organophosphate insecticides - insecticide resistance - non-spesific esterase -biochemical test.